Nano-featured poly (lactide-co-glycolide)-graphene microribbons as a promising substrate for nerve tissue engineering. (15th September 2019) - Aval, Negar Abbasi; Emadi, Rahmatollah; Valiani, Ali; Kharaziha, Mahshid; Karimipour, Mohammad; Rahbarghazi, Reza
Abstract: In this research, nanocomposite poly (lactide- co -glycolide)-Graphene (PLGA-Gr) microribbons were developed for neural tissue engineering. Moreover, the effects of Gr concentration (0, 0.1, 0.5 and 1 wt %) on the chemical and physical structure, mechanical properties, thermal stability and biological properties were evaluated. Our findings proved that incorporation of Gr nanosheets in the PLGA matrix resulted in the formation of aligned groove-shaped roughness on the surface of microribbons. In addition, Gr nanosheets could significantly promote the electrical conductivity and hydrophilicity of PLGA microribbons. In addition, the tensile strength and elastic modulus of the PLGA-Gr microribbons significantly promoted (upon 2 times and more than 3 times, respectively) compared to PLGA microribbons. The results demonstrated enhanced differentiation rate of SH-SY5Y cells to mature neurons on PLGA-Gr compared to PLGA. In summary, our findings discovered that aligned PLGA-Gr microribbons presented appropriate chemical, physical and mechanical properties to promote neuroblastoma cells. It is anticipated that the offered PLGA-Gr scaffolds might have great potential to develop a favorable construct for central nerve regeneration. However, further biological in vivo studies are required to assess the role of PLGA-Gr microribbons on the nerve regeneration.